Concluding remarks: Nutritional strategies to support the adaptive response to prolonged exercise training - van Loon, L. J. C.; Tipton, K. D. (Nutritional Coaching Strategy to Modulate Training Efficiency, 2013)
Nutrition plays a key role in allowing the numerous training hours to be translated into useful adaptive responses of various tissues in the individual athlete. Research over the last decade has shown many examples of the impact of dietary interventions to modulate the skeletal muscle adaptive response to prolonged exercise training. Proper nutritional coaching should be applied throughout both training and competition, each with their specific requirements regarding nutrient provision. Such dietary support will improve exercise training efficiency and, as such, further increase performance capacity. Here, we provide an overview on the properties of various nutritional interventions that may be useful to support the adaptive response to exercise training and competition and, as such, to augment exercise training efficiency.